PEMANFAATAN DANA ZAKAT PRODUKTIF DAN DAMPAKNYA TERHADAP PENDAPATAN MUSTAHIK - Umuri, Khairil (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Zakat plays a role in realizing socio-economic justice and poverty alleviation through job creation and entrepreneurial opportunities. Zakat given to mustahik will support their economic improvement if it is channeled to productive activities. One area of ​​productive zakat utilization is business capital assistance. The purpose of this study was to determine the impact of the use of productive zakat funds by Baitul Mal in Banda Aceh City on the income level of mustahik in Banda Aceh City. This research uses descriptive qualitative method. The results showed that the venture capital assistance program managed by Baitul Mal had no impact on the mustahik's income level. This is due to several things, namely mustahik's not being able to develop their business optimally, lack of supervision and assistance for mustahik's businesses, and declining sales during this pandemic. Therefore, comprehensive support is needed from various parties such as the government, the community and other institutions that support poverty alleviation programs).